The fate of Polish officers imprisoned in the NKVD prisoner-of-war camp Kozelsk “2” in the light of the account of Lieutenant Paweł Delalicz de Laval - JACZYŃSKI, Stanisław (Historia i Świat, 2025)
The document presents the conditions in which Polish officers captured by the NKVD in the summer of 1940 from internment camps in Lithuania were held in the prisoner-of-war camp in Kozelsk. The author included in his account his own impressions and observations regarding everyday life in the camp, as well as the Soviet personnel.